Comparison between the Effectiveness Fecal Immunochemical Test and Colonoscopy As A Tool For Colorectal Cancer Early Detection - Yossi Andila; Reno Rudiman; Andriana Purnama (Faculty of Medicine, Universitas Padjadjaran, 2022)
Cancer is a disease that causes a lot of misery and death in humans. According to data from the World Health Organization (WHO) in 2015, there are 8.8 million deaths caused by cancer and colorectal cancer ranked third with 774,000 deaths. One of the prevention effort for colorectal cancer is early detection in the population, especially in high-risk groups and in groups with non-specific symptoms. In general, two types of early detection tests are available: stool-based testing and structural testing. Fecal immunochemical test (FIT) is one type of examination that is categorized as the tool-based test. Meanwhile, the structural test include colonoscopy, CT colonography and flexible sigmoidoscopy. This study aimed to determine difference in the effectiveness of FIT against colonoscopy as an early detection tool for colorectal cancer. This study was a cross-sectional comparative diagnostic analytical observational study to compare FIT to colonoscopy for early detection of colorectal cancer. This study involved patients presented to Dr. Hasan Sadikin General Hospital Bandung, Indonesia. Analysis of diagnostic test data was carried out to obtain the sensitivity, specificity, and the positive and negative predictive values through the use of bivariate analysis in the form of Man Whitney test. Thirty-eight patients were included in this study, consisting of 27 cancer patients and 11 non-cancer patients. Results showed that the sensitivity level of FIT was 81.5%, with 72.7% specificity. There is no significant difference in the effectiveness between FIT and colonoscopy in screening for colorectal cancer.